Pengembangan Konseling Behavioral Teknik Kontrak Perilaku Untuk Meningkatkan Kedisiplinan Belajar Siswa SMP - Ida Bagus Putu Wibawa Ganda Manuaba; Putu Ari Dharmayanti; Luh Putu Sri Lestari (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This study aims to determine the design or construction of the guidebook development, to determine the validity of the instrument/content validity regarding the development of the guidebook and to determine the effectiveness of developing a behavioral counseling guidebook for behavioral contracting techniques to improve the learning discipline of junior high school students. This study is of the type of development research through the use of 4D development procedures (Define, Design, Develop, and Disseminate). The following study involved 3 experts (FIP Undiksha Counseling Lecturers) and 3 practitioners in the field of counseling guidance (BK teachers at SMP Negeri 1 Sukasada) who were tasked with testing the usability, feasibility, and accuracy of the manual. The research data were collected with expert validity instruments which were then analyzed using the Content Validity Ratio, Content Validity Index, and t-test formulas. The results of the CVR analysis show that all statements of instrument items are acceptable and get a CVI score of 0.98 with a very appropriate category. Thus, the behavioral counseling guidebook for behavioral contracting techniques meets the requirements for use. Testing the effectiveness of the guidebook was conducted on 30 students using a one-group pre-test and post-test experimental design. According to the results of the pre-test, there were 6 students who had low learning discipline so that the researchers provided group counseling services. Significance score The t-test result was 0.013, which means that the development of a behavioral counseling guidebook for behavioral contracting techniques is effective in increasing the learning discipline of junior high school students. To other researchers, it is better if the results of the research on the development of this counseling guidebook can be used as a reference regarding the problems to be investigated further, especially those related to student learning discipline, but still with various sources as consideration for carrying out a similar development. Abstrak: Penelitian ini bertujuan untuk mengetahui rancang bangun atau kontruksi pengembangan buku panduan, mengetahui validitas instrument/validitas isi mengenai pengembangan buku panduan serta mengetahui keefektifan pengembangan buku panduan konseling behavioral teknik kontrak perilaku untuk meningkatkan kedisiplinan belajar siswa SMP. Kajian ini berjenis penelitian pengembangan melalui penggunaan prosedur pengembangan 4D (Define, Design, Develop, dan Disseminate). Kajian berikut memperlibatkan 3 ahli (dosen bimbingan konseling FIP Undiksha) dan 3 orang praktisi di bidang bimbingan konseling (Guru BK SMP Negeri 1 Sukasada) yang bertugas untuk menguji kegunaan, kelayakan, dan ketepatan buku panduan. Data penelitian dikumpulkan dengan instrument validitas pakar yang selanjutnya dilakukan analisis menggunakan formula Content Validity Ratio, Content Validity Indeks, dan t-tes. Hasil analisis CVR menunjukan semua pernyataan item instrument berterima dan mendapat skor CVI sejumlah 0,98 dengan katagori sangat sesuai, Dengan begitu buku panduan konseling behavioral teknik kontrak perilaku terpenuhi ketentuan untuk digunakan. Pengujian efektivitas buku panduan dilakukan kepada 30 peserta didik mempergunakan disain eksperimen one grup pre-test dan post-test. Sesuai hasil dari pre-test terdapat 6 siswa yang memiliki kedisiplinan belajar yang rendah sehingga peneliti memberikan layanan konseling kelompok. Skor signifikansi Hasil uji-t 0,013 yang bermakna pengembangan buku panduan konseling behavioral teknik kontrak perilaku mempunyai keefektivan guna meningkatkan kedisiplinan belajar siswa SMP. Kepada peneliti lain maka sebaiknya hasil penelitian pengembangan buku panduan konseling ini dapat dijadikan refrensiterkait masalah-masalah yang akan diteliti selanjutnya terutama terkait dengan kedisiplinan belajar siswa, namun tetap dengan sumber beragam sebagai pertimbangan untuk melakukan sebuah pengembangan yang sejenis.